2017
DOI: 10.1099/jgv.0.000665
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 receptor antagonist: an early immunomodulatory cytokine induced by porcine reproductive and respiratory syndrome virus

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) infection poorly induces pro-inflammatory cytokines (IL-1, IL-6 and TNF-α) and type I IFN production during the early phase of infection. Our microarray analysis indicated strong upregulation of the IL1RA gene in type 2 PRRSV -infected monocyte-derived dendritic cells. Interleukin-1 receptor antagonist (IL-1Ra) is an early inhibitory cytokine that suppresses pro-inflammatory cytokines and T-lymphocyte responses. To investigate the induction of IL-1Ra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Interleukin-1 receptor antagonist (IL-1Ra) is known as an early inhibitory cytokine, which potentially participates in PRRSV-induced immunosuppression during the early phase of infection (26). As several reports showed that IL-1Ra is a potent negative immunomodulator of both innate and adaptive immune functions (5153), the present study extended the characterization of the negative immunomodulatory effects of PRRSV-induced IL-1Ra on several aspects of porcine immune functions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interleukin-1 receptor antagonist (IL-1Ra) is known as an early inhibitory cytokine, which potentially participates in PRRSV-induced immunosuppression during the early phase of infection (26). As several reports showed that IL-1Ra is a potent negative immunomodulator of both innate and adaptive immune functions (5153), the present study extended the characterization of the negative immunomodulatory effects of PRRSV-induced IL-1Ra on several aspects of porcine immune functions.…”
Section: Discussionmentioning
confidence: 99%
“…Although our observations on the negative immunomodulatory effects of PRRSV-induced IL-1Ra were obtained using in vitro assays, these circumstances are likely relevant to PRRSV-induced immunosuppression in the infected pigs in regard to impaired innate cytokine production (16, 92), prolonged PRRSV-specific T helper and CTL induction (93), and enhanced PRRSV-specific Treg population (22, 24, 94). In contrast, highly pathogenic (HP)-PRRSV infection, which is deficient in its ability for IL-1Ra induction (26), causes robust innate cytokine production in an early phase of infection (95). These findings support our notion that IL-1Ra is, in part, responsible for negative immune responses in the PRRSV-infected pigs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proinflammatory cytokines (TNF-a, IL-1 and IL-6) are induced after infection by PRRSV (Nedumpun et al 2017). PRRSV tends to attack the lungs and lymphoid organs and can proliferate in a variety of cells, such as porcine alveolar macrophages (PAMs), bone marrow-derived dendritic cells (BMDCs) and MARC-145 cells (Duan et al 1997;Gao et al 2016;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%